Recent developments of membranes and electrocatalysts for the hydrogen production by anion exchange membrane water electrolysers: A review - Kishore Chand; Ombretta Paladino (Arabian Journal of Chemistry, 2023)
Hydrogen production using anion exchange membrane water electrolysis (AEMWE) offers hope to the energy crisis faced by humanity. AEM electrolysis can be coupled with intermittent and renewable energy sources as well as with the use of low-cost electrocatalysts and other low-cost stack components. In AEM water electrolysis, one of the biggest advantages is the use of low-cost transition metal catalysts instead of traditional noble metal electrocatalysts. AEMWE is still in its infancy despite irregular research on catalysts and membranes. In order to generate commercially viable hydrogen, AEM water electrolysis technology must be further developed, including energy efficiency, membrane stability, stack feasibility, robustness, ion conductivity, and cost reduction.An overview of studies that have been conducted on electrocatalysts, membranes, and ionomers used in the AEMWE is here reported, with the aim that AEMWE research may be made more practical by this review report, by bridging technological gaps and providing practical research recommendations, leading to the production of scalable hydrogen.